The Performance of Sweet Corn and Selected Legumes in Weeded and Nonweeded Intercropping Systems - Katang, Ahmad (1989)
An intercropping study was conducted at the Agronomy Field Research Station, Universiti Pertanian Malaysia from January to April, 1987 involving sweet corn (Zea mays [L.] var. Thai Super Sweet), mungbean ( Phaseolus radiatus [L.] Wilczek var. VC-1163), cowpea (Vigna unguiculata [L .] var. Purple Hull Pink-Eyed Seed) and groundnut (Arachis hypogaea [L .]var. V-13) in weeded and nonweeded sweet corn + legume systems. Sweet corn was the base crop with mungbean, cowpea or groundnut as the intercrop in the respective weeded and nonweeded treatment combinations. The treatments were replicated four times in a randomised complete block design (ReBD) with factorial arrangements. The objectives of the study were to evaluate crops performance under weeded and nonweeded conditions, compatibility of the legumes with sweetcorn, comparative ability of the legumes to smother weeds, and the influence of the cropping system on the N, P and K contents of crops and weeds at harvest.